1968
DOI: 10.2172/4811535
|View full text |Cite
|
Sign up to set email alerts
|

Refrigerant Forced-Convection Condensation Inside Horizontal Tubes.

Abstract: Experimental data was obtained for the flow rate from 240,000 to 485,000 lbm/ft2 hr. R-22 was condensed in a 0.493" I.D. 18 ft. long test section. The measured heat transfer coefficients agreed with the prediction within 10% except a few points in the very low quality region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
2

Year Published

1974
1974
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 8 publications
5
27
0
2
Order By: Relevance
“…It should be noted that these correlations were restricted to a particular range of flow conditions. Bae et al (1969Bae et al ( , 1971 confirmed the validity of this correlation. Magiros and Dukler (1961).…”
Section: Introductionsupporting
confidence: 67%
“…It should be noted that these correlations were restricted to a particular range of flow conditions. Bae et al (1969Bae et al ( , 1971 confirmed the validity of this correlation. Magiros and Dukler (1961).…”
Section: Introductionsupporting
confidence: 67%
“…The annular film model developed follows the basic elements set up by Rohsenow and coworkers (Rohsenow et al 1956, Bae et al 1971, Traviss et al 1973. A turbulent vapor core is assumed to be surrounded by a uniform liquid film.…”
Section: Liquidmentioning
confidence: 99%
“…Сравнение экспериментальных данных с рас-четными, основанными на аналогичных моделях, описанных выше, показали хорошую сходимость экспериментальных α, полученных в работах [2,3], напротив в работе [4] наблюдалось отклонение экс-периментальных данных от расчетных при х > 0,5 ÷ 0,6.…”
Section: сравнение теоретических (полу-эмперических) решений с экunclassified
“…Для расчета параметров ручья и теплоотда-чи в нeм имеется несколько решений. Для расчета теплоотдачи при кольцевом течении пленки под дей-ствием скорости пара существует теоретические ре-шение Нуссельта для ламинарного течения пленки конденсата [1], а также несколько решений для турбу-лентной пленки, например в работах [2][3][4][5][6].…”
Section: Introductionunclassified